Influence of intracoronary injections of bone-marrow-derived mononuclear cells on large myocardial infarction outcome: Quantum of initial necrosis is the key - Obradović Slobodan; Balint Bela; Romanović Radoslav; Trifunović Zoran; Rusović Siniša; Baškot Branislav; Dopuđa Marija; Trifunović Gordana; Rafajlovski Sašo; Jung Robert; Gligić Branko (Vojnosanitetski Pregled)
Background/Aim. Autologous bone-marrow-derived intracoronary injection of mononuclear cells (MNC) modestly improved left ventricular ejection fraction (LVEF) in the selected patients after acute ST elevation myocardial infarction (STEMI). Major determinants of stem cell therapy outcome in the subacute phase of STEMI still remain unknown. Therefore, the aim of this study was to determine modifying factors for the outcome of stem cell therapy after STEMI. Methods. Eighteen patients in the stem cell therapy group and 24 patients in the control group with the successfully reperfused first large STEMI (LVEF ≤ 40%) were enrolled in the study. The stem cell group was submitted to autologous bone-marrow-derived MNC injection between 7-12 days after MI. Left ventricular ejection fraction and infarction size at baseline and after 4 months were determined by echocardiography and scintigraphy examination. Age, pain onset to reperfusion time, admission glycemia, maximum lactate dehydrogenase (LDH) activity and C-reactive protein level, baseline LVEF and infarction size, and the number of MNC injected were compared between patients with and without significant improvement of LVEF and decrease of myocardial infarct size after 4 months. Results. In the stem cell group, patients with the improvement of LVEF for more than 5.1% had significantly lower levels of LDH than patients without such improvement (1689 ± 139 vs 2133 ± 215 IU/L, p < 0.001) and lower baseline infarction size on scintigraphy (26.7 ± 5.2 vs 34.9 ± 3.7%, p < 0.001). Such dependence was not found in the control group. Conclusion. In the patients with first large STEMI intracoronary injection of autologous bone-marrow-derived MNC leads to the significant decrease of myocardial infarction size but not the significant improvement of LVEF after four months. Higher serum LDH levels after STEMI and very large baseline infarction size are predictors of failure of stem cell therapy in our group of STEMI patients.